2022
DOI: 10.1007/s12975-022-01106-4
|View full text |Cite
|
Sign up to set email alerts
|

Meta-review on Perforation Model of Subarachnoid Hemorrhage in Mice: Filament Material as a Possible Moderator of Mortality

Abstract: Robust preclinical models are inevitable for researchers to unravel pathomechanisms of subarachnoidal hemorrhage (SAH). For the mouse perforation model of SAH, the goal of this meta-review was the determination of variances in mortality, SAH severity grade, and vasospasm, and their experimental moderators, as many researchers are facing with incomparable results. We searched on the databases PubMed, Embase, and Web of Science for articles describing in vivo experiments using the SAH perforation mouse model and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 28 publications
0
8
1
Order By: Relevance
“…Indeed, existing literature in this review confirmed this vasospastic effect of blood in subarachnoid space with a reduction of cerebral arteries diameter of 47 to 89% with its peak at six to twelve hours after SAH and the reaching of pre-SAH values after four to seven days. Our systematic review and meta-analysis of the filament perforation SAH mouse model showed similar values for vasospasm from 50 to 90 percent of the non-SAH arteries diameters [20]. However, SAH-grade was not mentioned for the cisterna magna blood injection model in any of the included publication.…”
Section: Discussionmentioning
confidence: 74%
See 4 more Smart Citations
“…Indeed, existing literature in this review confirmed this vasospastic effect of blood in subarachnoid space with a reduction of cerebral arteries diameter of 47 to 89% with its peak at six to twelve hours after SAH and the reaching of pre-SAH values after four to seven days. Our systematic review and meta-analysis of the filament perforation SAH mouse model showed similar values for vasospasm from 50 to 90 percent of the non-SAH arteries diameters [20]. However, SAH-grade was not mentioned for the cisterna magna blood injection model in any of the included publication.…”
Section: Discussionmentioning
confidence: 74%
“…Thereby, the mortality rate after different periods of observation after SAH ranged from 0% to 22% at 24 hours after injection procedure into the cisterna magna with autologous blood displaying the overall trend of lower mortality rates compared to the filament perforation model of SAH which is around 20 to 30% [20,30]. As the vasospasm of large cerebral arteries is triggered through blood in the subarachnoid space to prevent the extravasation of a bigger amount of blood and increased ICP, we extracted data of arteries diameters in mice with and without injected autologous blood into the cisterna magna.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations